2014
DOI: 10.1021/jp506017a
|View full text |Cite
|
Sign up to set email alerts
|

Unambiguous Assignment of Reduction Potentials in Diheme Cytochromes

Abstract: Perturbed matrix method calculations are performed on a diheme cytochrome c (DHC) protein, in order to assign previously experimentally detemined reduction potentials (E) to their corresponding heme groups. Very good agreement between calculated values to experimental data prove that the present approach can be used as a predictive tool of redox thermodynamic properties of multicenter redox proteins in the absence of experimental data, or in synergy with state-of-the art spectroscopic and electrochemical appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 69 publications
(118 reference statements)
0
21
3
Order By: Relevance
“…Previous CpHMD publications using AMBER45 have already shown to under or overestimate pK a values by 1 unit or more, and such inaccuracy would certainly affect our ΔE o predictions.Our E,pH-REMD simulations clearly assign the experimental E o values of -240 and -310 mV respectively to the Nter heme and the Cter heme. This conclusion is in disagreement with a previous theoretical study performed by Daidone et al47 in which the opposite assignment was concluded. Regardless of any limitations that the theoretical approach used byDaidone et al might…”
contrasting
confidence: 99%
“…Previous CpHMD publications using AMBER45 have already shown to under or overestimate pK a values by 1 unit or more, and such inaccuracy would certainly affect our ΔE o predictions.Our E,pH-REMD simulations clearly assign the experimental E o values of -240 and -310 mV respectively to the Nter heme and the Cter heme. This conclusion is in disagreement with a previous theoretical study performed by Daidone et al47 in which the opposite assignment was concluded. Regardless of any limitations that the theoretical approach used byDaidone et al might…”
contrasting
confidence: 99%
“…Previous CpHMD publications using AMBER45 have already shown to under or overestimate pK a values by 1 unit or more, and such inaccuracy would certainly affect our ΔE o predictions.Our E,pH-REMD simulations clearly assign the experimental E o values of -240 and -310 mV respectively to the Nter heme and the Cter heme. This conclusion is in disagreement with a previous theoretical study performed by Daidone et al47 in which the opposite assignment was concluded. Regardless of any limitations that the theoretical approach used by Daidone et al might have, it is important to notice that in their simulations the protonation state of all pH-active residues was kept constant, however, as our E,pH-REMD simulations show, many pH-active residues titratable at pH 7.5, including the heme propionates, and this effect is certainly important for the proper description of the E o values.…”
contrasting
confidence: 99%
“…By such an approach, the free energy of several molecular processes—including redox potentials—in realistic environments have been modeled so far [ 16 , 51 , 52 , 53 , 54 , 55 , 56 ].…”
Section: Theoretical-computational Approachesmentioning
confidence: 99%